Atom-transfer radical cyclization of α-bromocarboxamides under organophotocatalytic conditions. (13th April 2021) - Tsuchiya, Naoki; Nakashima, Yusei; Hirata, Goki; Nishikata, Takashi
Graphical abstract: Highlights: Atom-transfer radical cyclization (ATRC) catalyzed by an organophotocatalyst. Reductive ATRC with Hantzsch ester. ATRC reactions of N -allyl-α-haloamides under visible-light irradiation in the presence of N -Ph-phenothiazine. Abstract: The atom-transfer radical cyclization (ATRC) reaction gives halogenated heterocycles from the corresponding halocarbonyls that possess a C–C double bond. In contrast, the reductive ATRC reaction gives non-halogenated heterocycles in the presence of a reductant. In this research, we successfully control the ATRC and reductive ATRC reactions of N -allyl-α-haloamides under visible-light irradiation in the presence/absence of the Hantzsch ester as a reductant.